THE PRACTICE OF OPTIMIZING THE LOGISTICS PROCESSES OF FOOD SUPPLY CHAINS - Danylenko, Valerii (Social Economics, 2021)
The article presents in general terms the reasons for increasing the importance of logistics processes optimizing mechanisms’ development concerning the food supply chain participants, as well as the current trends in the development of the business environment that encourage research in this area. In this paper, I define the functional boundaries The functional boundaries of the competencies’ implementation regarding the field of companies’ logistics management, I paid special attention to the framework for the implementation of production logistics competencies. I also disclosed the principle of interaction between the logistics system and the production system at an enterprise. This principle is meant to be implemented in the field of production planning and the gradual movement of resources, accompanied by the value creation. As a result of the abovementioned interaction, the essence of the mechanisms and tools of process management in the field of procurement logistics is revealed to achieve a synergistic effect from the continuity of management activities. This explains the reasons why the implementation of lean manufacturing tools indirectly leads to the optimization of logistics processes. Next, the essence of the lean production concept is revealed and arguments are given for the complementarity of the concept with the tools of logistics management, but taking into account the differences in their functional contents. The subject of this study is the Kanban lean production method, so the next stage of the discussion is devoted to the analysis of the theoretical provisions of this management concept. The principle of implementation of the discussed concept in the production practice is also schematically presented. Based on review studies results about the Kanban system practical application success, conclusions were drawn about the possible positive effects of this system’ application. Further, as a result of the analysis of a food supply chain participating company’s financial statements, I determined the daily residual inventory for one of the finished products items, and it was compared with the daily order sizes. Subsequently, with the use of the Kanban system, logistics processes were optimized by eliminating excess production. Finally, I summarized the results with a list of the potential benefits brought by the use of lean manufacturing tools.